CP-25 exerts a protective effect against ConA-induced hepatitis via regulating inflammation and immune response - Li, Nan; Wu, Jing-Jing; Qi, Meng; Wang, Zi-Ying; Zhang, Sheng-Nan; Li, Xiu-Qin; Chen, Ting-Ting; Wang, Mei-Fang; Zhang, Ling-Ling; Wei, Wei; Sun, Wu-Yi (Frontiers in Pharmacology, 2022)
Hepatitis is a common pathological basis for a variety of clinical liver diseases, which can eventually lead to liver failure and even potentially be life threatening. Paeoniflorin-6’-O-benzene sulfonate (CP 25) has proven to have critical anti-inflammatory effects in arthritis. However, the effect of CP 25 on hepatitis remains unclear. In this study, mice were intragastrically administered with CP-25 (25, 50 and 100 mg/kg), and then ConA (25 mg/kg) was intravenous injected to establish hepatitis model in vivo. Our results showed that CP 25 administration attenuated liver damage and decreased ALT and AST activities in mice with hepatitis. CP 25 modulated immune responses including down-regulated the proportions of activated CD4+, activated CD8+ T cells, and ratio of Th1/Th2 in ConA injected mice. CP 25 significantly inhibited IFN-γ, TNF-α production and suppressed the activation of MAPK signaling pathway influenced by ROS after ConA injection. In ConA stimulated RAW264.7 cells, CP 25 suppressed inflammatory cytokines secretion and reduced ROS level, which were consistent with animal experiments. Furthermore, the data showed that CP 25 restrained phosphorylation of ROS downstream ERK, JNK and p38 MAPK pathways, accompanied with inhibiting nuclear translocation of nuclear factor-kappaB (NF κB). In conclusion, our findings indicated that CP 25 protected against ConA induced hepatitis by modulating immune responses and attenuating ROS mediated inflammation may be through the MAPK/NF-κB signaling pathway.